PENYUSUNAN ANGGARAN KOMPREHENSIF SEBAGAI ALAT PERENCANAAN DAN PENGENDALIAN LABA PADA COFFEE SHOP BK23SPACE - Nyak Angeli Ajianing; Khairunnisa Khalida; Abdillah Fuad; Dini Vientiany (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This study aims to analyze the preparation of a comprehensive budget as a tool for profit planning and profit control at BK23Space Coffee Shop. The comprehensive budget is designed to provide an overall picture of business activities, including sales planning, production, raw material usage, labor costs, cash flow management, and profit projections. This research employs a quantitative descriptive method using sales and operational cost data obtained through observation and documentation. The results show that BK23Space sets a sales target of 1,200 cups per month at a selling price of IDR 20,000 per cup, generating monthly revenue of IDR 24,000,000 or IDR 72,000,000 per quarter. Based on the prepared production and cost budgets, the business is able to generate a net profit of IDR 8,000,000 per quarter with a net profit margin of 11.1% and has exceeded its Break Even Point (BEP). However, the cash budget analysis indicates a monthly cash deficit of IDR 5,000,000, highlighting the need for better cost control and more effective cash management. Overall, the comprehensive budget plays an important role in supporting management decisions, evaluating financial performance, and identifying potential risks and improvement opportunities to ensure business sustainability.